1998
DOI: 10.3181/00379727-218-44270
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cytokine Production by Dehydroepiandrosterone (DHEA) Plus Melatonin (MLT) Supplementation of Old Mice

Abstract: Tissue levels of the antioxidants melatonin (MLT) and dehydroepiandrosterone (DHEA) decline with age, and this decline is correlated with immune dysfunction. The aim of the current study is to determine whether hormone supplementation with MLT and DHEA together would synergize to reverse immune senescence. Old (16.5 months) female C57BL/6 mice were treated with DHEA, MLT, or DHEA + MLT. As expected, splenocytes were significantly (P < 0.05) higher in old mice as compared to young mice. DHEA, MLT, and DHEA + ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 0 publications
2
29
1
3
Order By: Relevance
“…DHEA reverses the senescent phenotype (as defined by the pattern of cytokine secretion) in mice and enhances the effects of vaccination of old mice to hepatitis B (582). Application of DHEA together with melatonin may have a limited additive effect (583). There is a reported association in human as well as mice between decreased DHEA and increased IL 6 in the aged; furthermore, DHEA was shown to inhibit IL 6 secretion from mononuclear cells of the elderly (584).…”
Section: Hormonesmentioning
confidence: 97%
“…DHEA reverses the senescent phenotype (as defined by the pattern of cytokine secretion) in mice and enhances the effects of vaccination of old mice to hepatitis B (582). Application of DHEA together with melatonin may have a limited additive effect (583). There is a reported association in human as well as mice between decreased DHEA and increased IL 6 in the aged; furthermore, DHEA was shown to inhibit IL 6 secretion from mononuclear cells of the elderly (584).…”
Section: Hormonesmentioning
confidence: 97%
“…It has been suggested that weak androgens such as DHEA may reverse the age-associated dysregulation of the Th1/Th2 cytokine balance by increasing the production of Th1 cytokines, IL-2 and IFN-␥, with little or no effect on the Th2 cytokines, IL-4 and IL-10 [4,5]. However, it is important to note that a DHEA-induced enhancement of Th1 cytokine production is not consistently found among rodent studies and decreases of Th1 cytokines have also been reported [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using animal models have demonstrated that one of the steroids contained in the over-the-counter "androgenic dietary supplements," dehydroepiandrosterone (DHEA), may reverse the agerelated decline of immune function and provide protection from infection [6]. Aged mice treated with DHEA exhibit enhanced interleukin (IL)-2 and interferon (IFN)-␥ production with no effect on IL-4 or IL-10, perhaps reversing the age-associated change in Th1/Th2 cytokine balance [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies (Du et al 2001 ;Powell and Sonnenfeld 2006 ) showed that DHEA may be an important factor for increasing TH2 cytokine synthesis, which encourage vigorous antibody production and are commonly associated with antibody responses important for resisting infection, and decreasing TH1 and proinfl ammatory cytokine production. However, DHEA has shown an opposite effect in vivo in which a TH2 downregulation (or TH1 upregulation) associated with DHEA administration has been found in old or retrovirus-infected mice (Inserra et al 1998 ;Zhang et al 1999 ;Araghi-Niknam et al 1997 ) . These discrepancies may refl ect differences in assays used to determine DHEA effects on cytokine production or differences in animals used.…”
Section: Dheamentioning
confidence: 99%